History of Cholestasis Is Not Associated with Worsening Outcomes in Subsequent Pregnancy with Cholestasis - Sarker, Minhazur R.; Debolt, Chelsea A.; Canfield, Dana; Ferrara, Lauren (American Journal of Perinatology, 2024)
Objective Intrahepatic cholestasis of pregnancy is associated with adverse pregnancy outcomes including intrauterine fetal demise, spontaneous preterm labor, and meconium-stained amniotic fluid. Studies have yet to determine if patients with a history of pregnancy complicated by cholestasis had an association with more severe adverse outcomes in a subsequent pregnancy complicated by cholestasis.Study Design Retrospective cohort study of multiparous, singleton, nonanomalous live gestations complicated by cholestasis at Elmhurst Hospital Center from 2005 to 2019. We compared rates of adverse outcomes in multiparous pregnancies complicated by cholestasis with versus without prior cholestasis. Our primary outcome was rates of spontaneous preterm labor. Our secondary outcomes included rates of iatrogenic preterm birth, meconium-stained amniotic fluid, cesarean delivery for nonreassuring fetal heart tracing. Chi-square and multivariate regression tests were used to determine the strength of association. In all analyses, a p-value less than 0.05 and 95% confidence interval not crossing 1.00 indicated statistical significance. Mount Sinai Icahn School of Medicine Institutional Review Board approval was obtained for this project.Results Of the 795 multiparous pregnancies complicated by cholestasis, 618 (77.7%) had no prior history of cholestasis and 177 (23.3%) had prior history of cholestasis. Multiparous pregnancies with history of cholestasis had higher rates of prior preterm birth, earlier gestational age at diagnosis and delivery, and were more likely to receive ursodeoxycholic acid therapy. Pregnancies with history of cholestasis were not associated with spontaneous preterm labor in subsequent pregnancies with cholestasis, but history of cholestasis was associated with iatrogenic preterm birth and neonatal intensive care unit (NICU) admission. After adjusting for confounders, the association with iatrogenic preterm birth and NICU admission were no longer statistically significant. There was no significant association between history of cholestasis and other adverse obstetric outcomes.Conclusion Findings suggests that history of prior cholestasis is not associated with worsening outcomes in subsequent pregnancies complicated by cholestasis.Key Points
Keywords: cholestasis; hepatobiliary disease; bile acids; stillbirth